InterOpT: A new testing platform based on oneM2M standards for IoT systems - Demirel, Senay Tuna; Demirel, Mehmet; Dogru, Ibrahim; Das, Resul (Ieee, 2019)
Nowadays, with the developing technologies, IoT based solutions are increasing day by day. In the scope of this study, a test platform has been developed to test the IoT solutions developed by different companies according to oneM2M standards. The main objective of the study is to provide a national standardization for the control of IoT solutions. The developed InterOpT (InterOpability Tool) testing platform software tool is the automation system for controlling interoperability and compliance with standards on IoT network components. Based on the OneM2M IoT standard recognized by ETSI, this system performs the validity tests defined by the RFC and analyzes and automates the results. Provides interoperability and system audit reports on IoT structures. Improved testing platform, web and cloud-based service can offer. It can do traffic and stress tests especially for the system and it can also do log collection analysis automatically. The platform can support different embedded IoT protocols such as HTTP, CoAP, MQTT. As a result, with this project, we have developed a successful test automation platform that can perform interoperability and compliance tests by adhering to IoT protocols and OneM2M standards.
International Symposium on Networks, Computers and Communications (ISNCC) -- JUN 18-20, 2019 -- Istanbul, TURKEY
Keywords: IoT test platform; M2M; OneM2M; ETSI; CoAP; MQTT